ASYMMETRIC INFORMATION IN THE IPO UNDERWRITING PROCESS ON THE INDONESIA STOCK EXCHANGE: PRICING, INITIAL ALLOCATION, UNDERPRICING, AND PRICE STABILIZATION - Utamaningsih, Arni; Tandelilin, Eduardus; Husnan, Suad; Sartono, R. Agus (Journal of Indonesian Economy and Business, 2013)
This study examines the IPO trading based on asymmetric information among heterogeneousinvestors. An underwriter plays an active role in the process of the IPO where underpricing is acentral issue. The underwriter(s) manages the IPO trading by determining the offered pricerange and a discriminatory treatment between institutional and individual investors. Theunderwriter prioritizes institutional investors, especially when they show strong buying interestsat the time of book building. The results prove that underpricing is higher when the IPO pricingis closer to the upper limit of the price range. We find that underpricing is higher when the allocationof shares to institutional investors is larger.Keywords: asymmetric information, underpricing, IPO allocation, IPO pricing, price stabilization,excess return